Facing the inevitable? The public telecom monopoly's way of coping with deregulation. Issue 3 (3rd April 2017) - Nevalainen, Pasi
Abstract: The telecommunications industry has gone through a total restructure since the late 1970s, as state-owned national monopolies have given way to listed enterprises and competitive international markets. Scholars have explained wide-ranging privatisation and deregulation at a general level, but what happened to the former state-owned monopolies and how they adapted to the emerging business-oriented environment, has had with less scrutiny. It has been assumed that external factors caused these institutions to adapt a business approach, but did these organisations themselves have any significant power of decision in these processes? This article explains how one of these former state organisations, the Finnish Post and Telecommunications Department (PTL) was turned into the business enterprise 'Sonera'. The analysis focuses on the management's point of view. As the national telecommunications operator encountered international developments as a compelling external force, which turned it from a local office-holder into a recipient of international influences, PTL's management came to the conclusion that the organisation, in order to survive, had no other choice but to change. It virtually took a strategic decision to transform the department to meet new expectations. However, the state-owner's support was crucial. The change, although dependent on external factors, was to a large extent an endogenous, time-consuming but accelerating process. Failure might have resulted in the PTL's defeat. Eventually the change became a self-fulfilling, 'inevitable' process which for one's part strengthened the international trend.